Political Marketing, or how to win elections? - Rudnik, Mariusz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2021)
The subject of the presented article is the problem of political marketing as a way to electoral victory. Marketing, promotion and advertising are useful instruments for achieving political goals. The ability to apply these means in practice is an expression of growing professionalism in the field of political knowledge. Marketing instruments are useful not only during election campaigns, but also in the everyday activities of political leaders, social institutions, political parties, trade unions and other participants in political life. This may concern the design and practical application of various political strategies, creating the image of a politician of a newly established political organisation, advertising to the public the government's policy of significant importance for the state or promoting the image of a country, city or region . In recent decades, election campaigns have taken on a permanent character, not being limited as before to the closed periods immediately preceding voting. Thus, knowledge of marketing has become more important in the political environments of modern countries. The adaptation of professional marketing techniques to the sphere of political action and the use of the potential of modern media have significantly influenced the way politics is conducted. The goals, methods and strategy of a political campaign are, in a sense, determined by the audience and the media. The American campaign model has become a model for many countries, especially those – like Poland – which have embarked on the path of democratic transformation after 1989.

Przedmiotem prezentowanego artykułu jest problematyka marketingu politycznego jako drogi do zwycięstwa wyborczego. Marketing, promocja i reklama to przydatne instrumenty do osiągania celów politycznych. Umiejętność stosowania tych środków w praktyce jest wyrazem rosnącego profesjonalizmu w dziedzinie wiedzy politycznej. Instrumenty marketingowe przydają się nie tylko podczas kampanii wyborczych, ale także w codziennej działalności liderów politycznych, instytucji społecznych, partii politycznych, związków zawodowych i innych uczestników życia politycznego. Może to dotyczyć projektowania i praktycznego stosowania różnych strategii politycznych, kreowania wizerunku polityka nowo powstałej organizacji politycznej, reklamowania opinii publicznej polityki rządu o istotnym znaczeniu dla państwa czy promowania wizerunku kraju, miasta lub regionu . W ostatnich dziesięcioleciach kampanie wyborcze nabrały charakteru permanentnego, nie ograniczając się jak dotychczas do okresów zamkniętych bezpośrednio poprzedzających głosowanie. Tym samym wiedza o marketingu nabrała większego znaczenia w środowiskach politycznych współczesnych krajów. Dostosowanie profesjonalnych technik marketingowych do sfery działań politycznych oraz wykorzystanie potencjału współczesnych mediów w istotny sposób wpłynęło na sposób prowadzenia polityki. O celach, metodach i strategii kampanii politycznej w pewnym sensie decydują publiczność i media. Model kampanii amerykańskiej stał się wzorem dla wielu krajów, zwłaszcza tych - jak Polska - które weszły na drogę przemian demokratycznych po 1989 roku.
Keywords: political marketing; presidential campaigns; Poland; voters; election; marketing polityczny; kampanie prezydenckie; Polska; wyborcy; wybory